The power of empathy [videorecording] (Australia: Ash Quarry Productions, 2001)
Psychologists Eve Ash and Peter Quarry discuss the importance of empathy, for our work environment and our personal well-being. Empathy is both a skill and an attitude. How can we best use the power of empathy when dealing with emotions? All roles require empathy * Customer service * Team members, leaders, managers, supervisors * Empathy as a skill * Empathy as an attitude * Am I an empathic person?